Test of the Effectiveness of Using Hibiscus Rosa Sinensis-L Extract as an Alternative to 2% Eosin in Examining Soil Transmitted Helminth Worm Eggs: Uji Efektivitas Penggunaan Sari Bunga Kembang Sepatu (Hibiscus Rosa Sinensis-L) Sebagai Alternatif Pengganti Eosin 2% Pada Pemeriksaan Telur Cacing Soil Transmitted Helminths - Ningsih, Rahma; Salnus, Subakir; Harmawati Novriani, Andi (Program Studi Farmasi, 2023)
Beckground Soil Transmitted Helminths infection is a type of parasite that causes worm infections, which are found in the human intestine and can be transmitted through the soil. Eosin 2% is a substance used to color worm eggs. Hibiscus flower (Hibiscus rosa-sinesis L) is one of the plants that can be used as an alternative dye for examination of Soil Transmitted Helminths (STH) worm eggs because it contains anthocyanin. Destination The purpose of this study was to find out that hibiscus flower extract (Hibiscus rosa-sinesis L) can be used as an alternative stain for microscopic examination of Soil Transmitted Helminths worm eggs. This research is a descriptive study by examining worm eggs using the direct method which was carried out by dyeing hibiscus flower extract with distilled water as a solvent and 2% eosin as a control. Results Hibiscus flower juice with a concentration of 1:1 is good for use as an alternative to 2% eosin in the examination of soil transmitted helminths eggs.